New evidence of baobab (Adansonia digitata) pounding by western chimpanzees (Pan troglodytes verus) - Carlota F. Galán-Plana; Andreu Sánchez-Megías; Justinn Renelies-Hamilton; Manuel Llana; Samba Diallo; Amanda Barciela; Laia Dotras; Jordi Galbany; R. Adriana Hernandez-Aguilar (Primates, 2026)
Percussive technology in wild chimpanzees ( Pan troglodytes ) shows significant behavioral variation across Africa. An example is baobab ( Adansonia digitata ) fruit pounding, which is only known to occur in the Bandafassi Arrondissement in the Kedougou region (Senegal) and in the Bafing area (Mali). The extent to which this proto-tool use behavior varies between populations is poorly understood. Here, we present a preliminary report of the baobab-pounding behavior of savanna chimpanzees from Dindefelo, Senegal. During the peak baobab fruiting season from November 2021 to January 2022, we obtained evidence of baobab pounding, both primate archaeological evidence (fruit remnants smeared on anvils and cracked, empty baobab shells) and camera trap recordings. We also studied chimpanzee baobab consumption using macroscopical fecal analysis. In addition, in the peak baobab fruiting season from 2019 to 2020, we opportunistically obtained hand-held camera videos of baobab pounding. Dindefelo chimpanzees opened baobab using two pounding and one non-percussive techniques. We recorded all age and sex classes performing baobab pounding, although only adolescents and adults succeeded in opening the fruit. Baobab pounding occurred on the ground (against rocks and baobab roots) and on the trees (against baobab horizontal branches). The apes held the fruit by the stem or the pericarp while cracking it against an anvil. In addition, the fecal analysis data suggest that baobab seed reingestion is common at Dindefelo. These findings expand our knowledge on the diversity of chimpanzee baobab-pounding behavior.

Regulation of venom composition by the Australian funnel-web spider Hadronyche infensa is achieved via compartmentalised toxin production and venom metering - David Morgenstern; Brett Hamilton; Darren Korbie; Karl R. Clauser; Brian J. Haas; Greg Bowlay; Kjetil L. Voje; Alun Jones; Deon J. Venter; Glenn F. King; Eivind A.B. Undheim (Toxicon, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

‘Earth system engineers’ and the cumulative impact of organisms in deep time - Simon A.F. Darroch; Michelle M. Casey; Alison T. Cribb; Amanda E. Bates; Matthew E. Clapham; Dori L. Contreras; Matthew Craffey; Ivo A.P. Duijnstee; William Gearty; Nicholas J. Gotelli; Marcus J. Hamilton; Riley F. Hayes; et al. (Trends in Ecology & Evolution, 2025)

Estimating the air quality standard exceedance areas and the spatial representativeness of urban air quality stations applying microscale modelling - F. Martín; V. Rodrigues; J.L. Santiago; J. Sousa; J. Stocker; S. Janssen; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; R. San José; et al. (Science of The Total Environment, 2025)

Wave-influenced connectivity and transport in submerged coral canopies - J. F. Hamilton; S. G. Monismith; J. R. Koseff (Coral Reefs, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Improved estimation of aquaculture associated European introgression in a captive breeding program for endangered Atlantic salmon - Melissa K. Holborn; Tony Kess; Cameron M. Nugent; Nathalie N. Brodeur; Joke Adesola; Evan Cronmiller; Lorraine C. Hamilton; Ross A. Jones; Beth L. Lenentine; Anna MacDonnell; Meghan McBride; Amber Messmer; et al. (Conservation Genetics, 2025)
The rapid, range-wide decline in Atlantic salmon, Salmo salar , populations is well documented and has led to establishment of captive rearing and breeding programs in order to preserve populations. However, recovery potential may be limited by the inclusion of non-local genotypes, which can be both difficult to detect and quantify. In the genetically unique Inner Bay of Fundy population located in Canada, three Live Gene Bank programs have been established to aid recovery of this endangered conservation unit. Evidence of aquaculture associated non-local (i.e., European) introgression had previously been detected using small panels of microsatellite markers with limited power. Here we show how advances in sequencing and machine learning technologies can support a conservation program. We used machine learning and a corresponding panel of 301 SNPs to estimate individual-level proportions of European ancestry. To assess the degree of introgression in each program and to assess changes over time, fish were randomly selected across several program generations. Estimates were validated by genotyping a subset of individuals on a 220 K SNP array and using established admixture methods. Of the 1741 fish analyzed, only 48 were found to have European ancestry greater than the detection threshold. We found the amount of European ancestry was previously overestimated, and that very few wild-collected founder individuals had large proportions of European ancestry. Moreover, because European ancestry was introduced to Bay of Fundy populations via introgression from aquaculture escapees, these values represent the minimum amount of aquaculture introgression in these captive populations.

Exposure effects of synthetic glucocorticoid drugs on skeletal developmental and immune cell function in zebrafish - Charles M. Hamilton; Matthew J. Winter; Jonathan S. Ball; Maciej Trznadel; Luigi Margiotta-Casaluci; Stewart F. Owen; Charles R. Tyler (Science of The Total Environment, 2024)

Genomic insights into hybrid zone formation: The role of climate, landscape, and demography in the emergence of a novel hybrid lineage - Constance E. Bolte; Tommy Phannareth; Michelle Zavala‐Paez; Brianna N. Sutara; Muhammed F. Can; Matthew C. Fitzpatrick; Jason A. Holliday; Stephen R. Keller; Jill A. Hamilton (Molecular Ecology, 2024)
Population demographic changes, alongside landscape, geographic and climate heterogeneity, can influence the timing, stability and extent of introgression where species hybridise. Thus, quantifying interactions across diverged lineages, and the relative contributions of interspecific genetic exchange and selection to divergence at the genome‐wide level is needed to better understand the drivers of hybrid zone formation and maintenance. We used seven latitudinally arrayed transects to quantify the contributions of climate, geography and landscape features to broad patterns of genetic structure across the hybrid zone of Populus trichocarpa and P. balsamifera and evaluated the demographic context of hybridisation over time. We found genetic structure differed among the seven transects. While ancestry was structured by climate, landscape features influenced gene flow dynamics. Demographic models indicated a secondary contact event may have influenced contemporary hybrid zone formation with the origin of a putative hybrid lineage that inhabits regions with higher aridity than either of the ancestral groups. Phylogenetic relationships based on chloroplast genomes support the origin of this hybrid lineage inferred from demographic models based on the nuclear data. Our results point towards the importance of climate and landscape patterns in structuring the contact zones between P. trichocarpa and P. balsamifera and emphasise the value whole genome sequencing can have to advancing our understanding of how neutral processes influence divergence across space and time.

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

A ring trial to harmonize Toxoplasma gondii microsatellite typing: comparative analysis of results and recommendations for optimization - M. Joeres; G. Cardron; K. Passebosc-Faure; N. Plault; M. Fernández-Escobar; C. M. Hamilton; L. O’Brien-Anderson; R. Calero-Bernal; L. Galal; C. Luttermann; P. Maksimov; F. J. Conraths; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
A ring trial among five European laboratories was organized to reach consistency in microsatellite (MS) typing of the zoonotic parasite Toxoplasma gondii . Three sample sets were circulated and analyzed by each laboratory following a previously published method that is based on fragment length polymorphism of 15 MS markers. The first sample set compared typing results in general and focused on effects of DNA concentration; the second sample set focused on the polymorphic fingerprinting markers that can differentiate T. gondii strains within the same archetypal lineage; and the third set focused on non-archetypal genotypes. Methodological variations between laboratories, including the software programs used to determine MS fragment length, were collated using a questionnaire. Overall, lineage-level typing results reached a high level of agreement, especially in samples with the highest DNA concentrations. However, laboratory-specific differences were observed for particular markers. Major median differences in fragment length, of up to 6 base pairs, were related to the fluorophore used to label fragment-specific primers. In addition, primer pairs with identical sequences obtained from different suppliers resulted in fragments of differing length. Furthermore, differences in the way the sequencing profiles were assessed and interpreted may have led to deviating results in fragment length determination. Harmonization of MS typing, for example, by using the same fluorophores or by numerical adjustments applied to the fragment-lengths determined, could improve the uniformity of the results across laboratories. This is the first interlaboratory comparison, providing guidelines (added as a supplement) for the optimization of this technique.

Great expectations: patients’ preferences for clinically significant results from genomic sequencing - Salma Shickh; Agnes Sebastian; Marc Clausen; Chloe Mighton; Christine Elser; Andrea Eisen; Larissa Waldman; Seema Panchal; Thomas Ward; June C. Carroll; Emily Glogowski; Kasmintan A. Schrader; et al. (Human Genetics, 2023)

Planktic foraminifera iodine/calcium ratios from plankton tows - Helge A. Winkelbauer; Babette A. A. Hoogakker; Rosie J. Chance; Catherine V. Davis; Christopher J. Anthony; Juliane Bischoff; Lucy J. Carpenter; Simon R. N. Chenery; Elliott M. Hamilton; Philip Holdship; Victoria L. Peck; Alex J. Poulton; et al. (Frontiers in Marine Science, 2023)
Planktic foraminifera test iodine to calcium ratios represent an emerging proxy method to assess subsurface seawater oxygenation states. Several core-top studies show lower planktic foraminifera I/Ca in locations with oxygen depleted subsurface waters compared to well oxygenated environments. The reasoning behind this trend is that only the oxidized species of iodine, iodate, is incorporated in foraminiferal calcite. The I/Ca of foraminiferal calcite is thought to reflect iodate contents in seawater. To test this hypothesis, we compare planktic foraminifera I/Ca ratios, obtained from plankton tows, with published and new seawater iodate concentrations from 1) the Eastern North Pacific with extensive oxygen depletion, 2) the Benguela Current System with moderately depleted oxygen concentrations, and 3) the well oxygenated North and South Atlantic. We find the lowest I/Ca ratios (0.07 µmol/mol) in planktic foraminifera retrieved from the Eastern North Pacific, and higher values for samples (up to 0.72 µmol/mol) obtained from the Benguela Current System and North and South Atlantic. The I/Ca ratios of plankton tow foraminifera from environments with well oxygenated subsurface waters, however, are an order of magnitude lower compared to core-tops from similarly well-oxygenated regions. This would suggest that planktic foraminifera gain iodine post-mortem, either when sinking through the water column, or during burial.

Quantifying Cardiothoracic Variation with Posture and Respiration to Inform Cardiac Device Design - Geeth A. Kondaveeti; Varun A. Bhatia; Ryan P. Lahm; Megan L. Harris; James P. Gaewsky; F. Scott Gayzik; John F. Greenhalgh; Craig A. Hamilton; R. Brandon Stacey; Ashley A. Weaver (Cardiovascular Engineering and Technology, 2023)

Conventional loose mineral with added red clover leaf (Trifolium pratense L.) reverses vasoconstriction associated with tall fescue toxicosis in steers - Brittany E. Davis; Tracy A. Hamilton; John T. Johns; David L. Harmon; James L. Klotz; Jennifer R. Weinert-Nelson; Jack P. Goodman; John May; Huihua Ji; F. Neal Schrick; Michael D. Flythe (Animal Feed Science and Technology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Venoms for all occasions: The functional toxin profiles of different anatomical regions in sea anemones are related to their ecological function - Lauren M. Ashwood; Eivind A. B. Undheim; Bruno Madio; Brett R. Hamilton; Marymegan Daly; David A. Hurwood; Glenn F. King; Peter J. Prentis (Molecular Ecology, 2022)
The phylum Cnidaria is the oldest extant venomous group and is defined by the presence of nematocysts, specialized organelles responsible for venom production and delivery. Although toxin peptides and the cells housing nematocysts are distributed across the entire animal, nematocyte and venom profiles have been shown to differ across morphological structures in actiniarians. In this study, we explore the relationship between patterns of toxin expression and the ecological roles of discrete anatomical structures in Telmatactis stephensoni . Specifically, using a combination of proteomic and transcriptomic approaches, we examined whether there is a direct correlation between the functional similarity of regions and the similarity of their associated toxin expression profiles. We report that the regionalization of toxin production is consistent with the partitioning of the ecological roles of venom across envenomating structures, and that three major functional regions are present in T . stephensoni : tentacles, epidermis and gastrodermis. Additionally, we find that most structures that serve similar functions not only have comparable putative toxin profiles but also similar nematocyst types. There was no overlap in the putative toxins identified using proteomics and transcriptomics, but the expression patterns of specific milked venom peptides were conserved across RNA‐sequencing and mass spectrometry imaging data sets. Furthermore, based on our data, it appears that acontia of T . stephensoni may be transcriptionally inactive and only mature nematocysts are present in the distal portions of the threads. Overall, we find that the venom profile of different anatomical regions in sea anemones varies according to its ecological functions.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Coastal Ocean Observing and Modeling Systems in Brazil: Initiatives and Future Perspectives - Guilherme Franz; Carlos A. E. Garcia; Janini Pereira; Luiz Paulo de Freitas Assad; Marcelo Rollnic; Luis Hamilton P. Garbossa; Letícia Cotrim da Cunha; Carlos A. D. Lentini; Paulo Nobre; Alexander Turra; Janice R. Trotte-Duhá; Mauro Cirano; et al. (Frontiers in Marine Science, 2021)
Coastal ocean observing and modeling systems (coastal observatories), connected with regional and global ocean systems, improve the quality of information and forecasts for effective management of safe and sustainable maritime activities. The public availability of systematic and long-term information of the ocean is an engine for the Blue Economy, boosting economic growth, employment, and innovation. An overview of some Brazilian initiatives is presented in this paper, involving universities, private companies, federal and state agencies, covering institutions from south to north of Brazil. Although these initiatives focus mainly on ocean physics, integrated efforts can extend the scope to include biogeochemistry and marine biodiversity, helping to address interdisciplinary problems. Existing initiatives can be connected, and new ones fostered, to fill in the gaps of temporal and spatial coverage of ocean monitoring in the vast oceanic area under Brazilian jurisdiction (nationally referred to as the Blue Amazon, in reference to the similar richness of the Amazon Forest). The alignment among national and regional initiatives, as well as with international programs, can be promoted if coordinated by a national-level organization, maximizing the return of public investment and socioeconomic benefits. In light of international examples, possible future institutional arrangements are discussed, leveraging from existing national public policies and international cooperation that Brazil is taking part. The United Nations Decade of Ocean Science for Sustainable Development is a timely opportunity to encourage an institutional arrangement to support and articulate an integrated network of coastal observatories in Brazil.

Prevalence and Genetic Diversity of Toxoplasma gondii in Free-Ranging Chickens from the Caribbean - C. M. Hamilton; R. Robins; R. Thomas; C. Oura; S. Oliveira; I. Villena; E. A. Innes; F. Katzer; P. J. Kelly (Acta Parasitologica, 2019)

A process of convergent amplification and tissue‐specific expression dominates the evolution of toxin and toxin‐like genes in sea anemones - Joachim M. Surm; Hayden L. Smith; Bruno Madio; Eivind A.B. Undheim; Glenn F. King; Brett R. Hamilton; Chloé A. van der Burg; Ana Pavasovic; Peter J. Prentis (Molecular Ecology, 2019)
Members of phylum Cnidaria are an ancient group of venomous animals and rely on a number of specialized tissues to produce toxins in order to fulfil a range of ecological roles including prey capture, defence against predators, digestion and aggressive encounters. However, limited comprehensive analyses of the evolution and expression of toxin genes currently exist for cnidarian species. In this study, we use genomic and transcriptomic sequencing data to examine gene copy number variation and selective pressure on toxin gene families in phylum Cnidaria. Additionally, we use quantitative RNA‐seq and mass spectrometry imaging to understand expression patterns and tissue localization of toxin production in sea anemones. Using genomic data, we demonstrate that the first large‐scale expansion and diversification of known toxin genes occurs in phylum Cnidaria, a process we also observe in other venomous lineages, which we refer to as convergent amplification. Our analyses of selective pressure on sea anemone toxin gene families reveal that purifying selection is the dominant mode of evolution for these genes and that phylogenetic inertia is an important determinant of toxin gene complement in this group. The gene expression and tissue localization data revealed that specific genes and proteins from toxin gene families show strong patterns of tissue and developmental‐phase specificity in sea anemones. Overall, convergent amplification and phylogenetic inertia have strongly influenced the distribution and evolution of the toxin complement observed in sea anemones, while the production of venoms with different compositions across tissues is related to the functional and ecological roles undertaken by each tissue type.

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

Impacts of a bivalve mass mortality event on an estuarine food web and bivalve grazing pressure - Hannah F. E. Jones; Conrad A. Pilditch; David P. Hamilton; Karin R. Bryan (New Zealand Journal of Marine and Freshwater Research, 2017)
Declines in bivalve populations have been quite common worldwide, often associated with coastal development, pollution and climate change. In addition to the impacts of these chronic stressors, occasional mass mortality events may have severe consequences on ecosystem services and biodiversity. In this study, we examined the impact of a mass mortality event of the clam ( Austrovenus stutchburyi ) on an estuarine food web and the grazing pressure exerted by the bivalve population. In February 2009, c. 60% of the clam population died in Whangateau Harbour, New Zealand. Population clearance rate calculations suggest that the clam population do not exert significant top‐down control on phytoplankton biomass in the estuary, and thus the impact of the mortality event on bivalve grazing pressure was less severe than the reduction in abundance would suggest. A trophic model shows that phytoplankton play a limited role in the estuary food web, which is instead dominated by microphytobenthos and clams. This study highlights the importance of microphytobenthos in shallow estuaries, and the application of the trophic model is a useful tool that can identify key components of the ecosystem and could help inform monitoring programmes.

Influence of Nrf2 activators on subcellular skeletal muscle protein and DNA synthesis rates after 6 weeks of milk protein feeding in older adults - Adam R. Konopka; Jaime L. Laurin; Robert V. Musci; Christopher A. Wolff; Justin J. Reid; Laurie M. Biela; Qian Zhang; Fredrick F. Peelor; Christopher L. Melby; Karyn L. Hamilton; Benjamin F. Miller (GeroScience, 2017)

Population‐level consequences for wild fish exposed to sublethal concentrations of chemicals – a critical review - Patrick B Hamilton; Ian G Cowx; Marjorie F Oleksiak; Andrew M Griffiths; Mats Grahn; Jamie R Stevens; Gary R Carvalho; Elizabeth Nicol; Charles R Tyler (Fish and Fisheries, 2016)
Concentrated chemical spills have been shown to impact adversely on fish populations and even cause localized population extinctions. Evaluating population‐level impacts of sublethal exposure concentrations is, however, complex and confounded by other environmental pressures. Applying effect measures derived from laboratory‐based chemical exposures to impacts in wild fish populations is constrained by uncertainty on how biochemical response measures (biomarkers) translate into health outcomes, lack of available data for chronic exposures and the many uncertainties in available fish population models. Furthermore, wild fish show phenotypic plasticity and local adaptations can occur that adds geographic and temporal variance on responses. Such population‐level factors are rarely considered in the chemical risk assessment process and can probably be derived only from studies on wild fish. Molecular technologies, including microsatellite and SNP genotyping, and RNAS eq for gene expression studies, are advancing our understanding of mechanisms of eco‐toxicological response, tolerance, adaptation and selection in wild populations. We examine critically the application of such approaches with examples including using microsatellites that has identified roach ( Rutilus rutilus ) populations living in rivers contaminated with sewage effluents that are self‐sustaining, and studies of stickleback ( Gasterosteus aculeatus ) and killifish ( Fundulus heteroclitus ) that have identified genomic regions under selection putatively related to pollution tolerance. Integrating data on biological effects between laboratory‐based studies and wild populations, and building understanding on adaptive responses to sublethal exposure are some of the priority research areas for more effective evaluation of population risks and resilience to contaminant exposure.

The role of defensive ecological interactions in the evolution of conotoxins - J. R. Prashanth; S. Dutertre; A. H. Jin; V. Lavergne; B. Hamilton; F. C. Cardoso; J. Griffin; D. J. Venter; P. F. Alewood; R. J. Lewis (Molecular Ecology, 2016)
Venoms comprise of complex mixtures of peptides evolved for predation and defensive purposes. Remarkably, some carnivorous cone snails can inject two distinct venoms in response to predatory or defensive stimuli, providing a unique opportunity to study separately how different ecological pressures contribute to toxin diversification. Here, we report the extraordinary defensive strategy of the Rhizoconus subgenus of cone snails. The defensive venom from this worm‐hunting subgenus is unusually simple, almost exclusively composed of αD‐conotoxins instead of the ubiquitous αA‐conotoxins found in the more complex defensive venom of mollusc‐ and fish‐hunting cone snails. A similarly compartmentalized venom gland as those observed in the other dietary groups facilitates the deployment of this defensive venom. Transcriptomic analysis of a Conus vexillum venom gland revealed the αD‐conotoxins as the major transcripts, with lower amounts of 15 known and four new conotoxin superfamilies also detected with likely roles in prey capture. Our phylogenetic and molecular evolution analysis of the αD‐conotoxins from five subgenera of cone snails suggests they evolved episodically as part of a defensive strategy in the Rhizoconus subgenus. Thus, our results demonstrate an important role for defence in the evolution of conotoxins.

Isolation and characterization of 29 microsatellite markers for the bumphead parrotfish, Bolbometopon muricatum, and cross amplification in 12 related species - Mark A. Priest; Glenn R. Almany; Camrin D. Braun; Richard J. Hamilton; Diego F. Lozano-Cortés; Pablo Saenz-Agudelo; Michael L. Berumen (Marine Biodiversity, 2015)

A rapid PCR-based test for identification of fifteen British bat species - P. B. Hamilton; T. M. Uren Webster; M. Basiewicz; E. V. Kennedy; E. S. R. De-Bastos; F. Mathews (Conservation Genetics Resources, 2015)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Challenges and opportunities for integrating lake ecosystem modelling approaches - Wolf M. Mooij; Dennis Trolle; Erik Jeppesen; George Arhonditsis; Pavel V. Belolipetsky; Deonatus B. R. Chitamwebwa; Andrey G. Degermendzhy; Donald L. DeAngelis; Lisette N. De Senerpont Domis; Andrea S. Downing; J. Alex Elliott; Carlos Ruberto Fragoso; et al. (Aquatic Ecology, 2010)

Variants in toll-like receptors 2 and 9 influence susceptibility to pulmonary tuberculosis in Caucasians, African-Americans, and West Africans - Digna Rosa Velez; Christian Wejse; Martin E. Stryjewski; Eduardo Abbate; William F. Hulme; Jamie L. Myers; Rosa Estevan; Sara G. Patillo; Rikke Olesen; Alessandra Tacconelli; Giorgio Sirugo; John R. Gilbert; et al. (Human Genetics, 2010)

NOS2A, TLR4, and IFNGR1 interactions influence pulmonary tuberculosis susceptibility in African-Americans - Digna Rosa Velez; William F. Hulme; Jamie L. Myers; J. Brice Weinberg; Marc C. Levesque; Martin E. Stryjewski; Eduardo Abbate; Rosa Estevan; Sara G. Patillo; John R. Gilbert; Carol D. Hamilton; William K. Scott (Human Genetics, 2009)

Measurement and calculation of OH reactivity at a United Kingdom coastal site - James D. Lee; Jennifer C. Young; Katie A. Read; Jacqueline F. Hamilton; James R. Hopkins; Alastair C. Lewis; Brian J. Bandy; James Davey; Peter Edwards; Trevor Ingham; Daniel E. Self; Shona C. Smith; et al. (Journal of Atmospheric Chemistry, 2009)

Evidence of a North Atlantic right whale calf ( Eubalaena glacialis ) born in northeastern U.S. waters - Melissa R. Patrician; Ingrid S. Biedron; H. Carter Esch; Frederick W. Wenzel; Lindsay A. Cooper; Philip K. Hamilton; Allison H. Glass; Mark F. Baumgartner (Marine Mammal Science, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Geographical Clustering of Pancreatic Cancers in the Northeast Nile Delta Region of Egypt - A. S. Soliman; X. Wang; J.-D. Stanley; N. El-Ghawalby; M. L. Bondy; F. Ezzat; A. Soultan; M. Abdel-Wahab; O. Fathy; G. Ebidi; N. Abdel-Karim; K.-Anh. Do; et al. (Archives of Environmental Contamination and Toxicology, 2006)

Use of amplified fragment length polymorphism markers to assess genetic diversity of Lolium species from Portugal - A. Cresswell; N. R. Sackville Hamilton; A. K. Roy; B. M. F. Viegas (Molecular Ecology, 2001)
We evaluated the use of amplified fragment length polymorphism (AFLP) markers to distinguish genotypes, populations and species of Lolium. Accessions of two species Lolium perenne and Lolium multiflorum and their hybrid Lolium × hybridum , collected by the Institute of Grass and Environmental Research in 1995 from locations across Portugal, were used. The genetic variation within and between populations from the extremes of latitude and altitude was determined and assessed. Three primer pair combinations generated 765 polymorphic bands. Principal coordinate analysis of similarities between 127 plants showed high dimensionality in the data. Axes 1–3 were associated primarily with species differences, axes 4–14 with population differences within species and axis 15 onwards with within population differences. UPGMA analysis confirmed the groupings. The three populations of L. perenne formed a discrete cluster widely separated from all other populations. There were two distinct groups of L. × hybridum , of which one was similar to and overlapped with L. multiflorum and the second formed a distinct cluster. Analyses of individual bands showed that every inter‐ and intraspecific contrast involved a different sets of bands, again confirming the high dimensionality of the data. No single band was strictly diagnostic of any population or species. Nevertheless, the UPGMA analysis showed little or no overlap between populations. Thus, despite the high ratio of within‐to‐between population genetic variance, the full AFLP banding pattern of each genotype is a relatively reliable fingerprint diagnostic of its parent population. The high dimensionality implies that many different factors contribute to the differences observed. This adds to the potential value of the methodology, since it implies that there is a reasonably high likelihood of finding bands relevant to a given environmental gradient or other factor influencing the distribution of genetic diversity.

Pollen‐based biome reconstruction for southern Europe and Africa 18,000 yr bp - H. Elenga; O. Peyron; R. Bonnefille; D. Jolly; R. Cheddadi; J. Guiot; V. Andrieu; S. Bottema; G. Buchet; J.‐L. De Beaulieu; A. C. Hamilton; J. Maley; et al. (Journal of Biogeography, 2000)
Pollen data from 18,000 14 C yr bp were compiled in order to reconstruct biome distributions at the last glacial maximum in southern Europe and Africa. Biome reconstructions were made using the objective biomization method applied to pollen counts using a complete list of dryland taxa wherever possible. Consistent and major differences from present‐day biomes are shown. Forest and xerophytic woods/scrub were replaced by steppe, both in the Mediterranean region and in southern Africa, except in south‐western Cape Province where fynbos (xerophytic scrub) persisted. Sites in the tropical highlands, characterized today by evergreen forest, were dominated by steppe and/or xerophytic vegetation (cf. today’s Ericaceous belt and Afroalpine grassland) at the last glacial maximum. Available data from the tropical lowlands are sparse but suggest that the modern tropical rain forest was largely replaced by tropical seasonal forest while the modern seasonal or dry forests were encroached on by savanna or steppe. Montane forest elements descended to lower elevations than today.

Ice Shelf Microbial Ecosystems in the High Arctic and Implications for Life on Snowball Earth - W. F. Vincent; J. A. E. Gibson; R. Pienitz; V. Villeneuve; P. A. Broady; P. B. Hamilton; C. Howard-Williams (The Science of Nature, 2000)

Evidence for spatial niche partitioning in predaceous aphidophaga: Use of plant colour as a cue - F. Lorenzetti; J. T. Arnason; B. J. R. Philogène; R. I. Hamilton (BioControl, 1997)

Characterization, scaling, and partial representation of diffuse and discrete input junctions to CA3 hippocampus - F. G. Ascarrunz; M. A. Kisley; K. A. Flach; R. W. Hamilton; R. J. MacGregor (Biological Cybernetics, 1995)

Characterization, scaling, and partial representation of diffuse and discrete input junctions to CA3 hippocampus - F. G. Ascarrunz; M. A. Kisley; K. A. Flach; R. W. Hamilton; R. J. MacGregor (Biological Cybernetics, 1995)

Similarities in the behaviour of Chernobyl derived Ru-103, Ru-106 and Cs-137 in two freshwater lakes - J. Hilton; W. Davison; J. Hamilton-Taylor; M. Kelly; F. R. Livens; E. Rigg; D. L. Singleton (Aquatic Sciences, 1994)

The replication of virulent and attenuated strains of African swine fever virus in porcine macrophages - R. C. Wardley; F. Hamilton; P. J. Wilkinson (Archives of Virology, 1979)